Chronic ankle instability: a meta-analysis and systematic review comparing clinical outcomes of anterior talofibular ligament repair with or without reinforcement of the lower extensor retinaculum - Liu, Haoyang; Li, Hongxu; Shen, Mengran; Zhou, Yu; Wang, Bailiang; Ma, Jinhui (Frontiers in Surgery, 2025)
BackgroundChronic ankle instability (CAI) is a prevalent condition often treated with the Broström procedure, sometimes modified by Gould. This study aims to compare the clinical outcomes of patients undergoing the Broström procedure with and without the Gould modification, focusing on the implications for CAI management.MethodsA comprehensive search was conducted across PubMed, EMBASE, Wiley Library, Science Direct, Europe PMC, and Scopus for studies comparing the Broström procedure with and without the Gould modification. The search spanned from the inception of these databases to October 12, 2024, using specific terms related to ankle instability and ligament repair.ResultsOur meta-analysis revealed that there was no significant difference in AOFAS scores, indicating a weak correlation between AOFAS scores and reinforcement of the Inferior Extensor Retinaculum (IER) [mean difference −1.14 (−2.16, −0.11), p = 0.03 I2:0%, p = 1.000]. Similarly, the reinforcement of IER showed a low correlation with Karlsson scores [mean difference −0.15 (−2.25, 1.96), p = 0.89; I2: 48%, p = 0.07]. The results for talar tilt [mean difference −0.11° (−0.37, 0.15), p = 0.42; I2:0%, p = 0.87] and anterior talar translation [mean difference 0.09 mm (−0.10, 0.29), p = 0.34; I2:0%, p = 0.91] were similar between the two groups at follow-up. The funnel plots for AOFAS scores, talar tilt, and complications were symmetrical, indicating no publication bias or other biases in the studies.ConclusionsThe findings suggest that for patients with CAI, the Broström procedure with or without the Gould modification yields comparable postoperative functional outcomes. This has significant implications for the surgical management of CAI, potentially simplifying treatment protocols.Level of evidence: Level II, systematic review of Level II studies.